(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This study explores the prospects for sustainable economic expansion in Uzbekistan through the lens of developing a green economy and identifies the influential factors shaping this trajectory. By embracing the principles of sustainability and environmental stewardship, Uzbekistan aims to unlock its green economy potential as a driver of long-term prosperity. Through a comprehensive analysis of key economic, environmental, and policy factors, this paper provides insights into the pathways for sustainable growth. It examines the role of renewable energy, green infrastructure, sustainable agriculture, and eco-friendly industries in fostering economic development while mitigating environmental impact. Additionally, it investigates the policy frameworks, institutional capacities, and socio-economic dynamics influencing the transition towards a green economy. By addressing these factors, Uzbekistan can chart a course towards sustainable economic expansion while balancing environmental preservation and socio-economic progress.